Global ionospheric and thermospheric response to the 5 April 2010 geomagnetic storm: An integrated data‐model investigation. Issue 12 (9th December 2014) - Lu, G.; Hagan, M. E.; Häusler, K.; Doornbos, E.; Bruinsma, S.; Anderson, B. J.; Korth, H.
Abstract: We present a case study of the 5 April 2010 geomagnetic storm using observations and numerical simulations. The event was driven by a fast‐moving coronal mass ejection and despite being a moderate storm with a minimum Dst near −50 nT, the event exhibited elevated thermospheric density and surges of traveling atmospheric disturbances (TADs) more typically seen during major storms. The Thermosphere‐Ionosphere‐Mesosphere‐Electrodynamics General Circulation Model (TIMEGCM) was used to assess how these features were generated and developed during the storm. The model simulations gave rise to TADs that were highly nonuniform with strong latitude and longitude/local time dependence. The TAD phase speeds ranged from 640 m/s to 780 m/s at 400 km and were 5% lower at 300 km and approximately 10–15% lower at 200 km. In the lower thermosphere around 100 km, the TAD signatures were nearly unrecognizable due to much stronger influence of upward propagating atmospheric tides. The thermosphere simulation results were compared to observations available from the Gravity Field and Steady‐State Ocean Circulation Explorer (GOCE), CHAllenging Minisatellite Payload (CHAMP) and Gravity Recovery and Climate Experiment (GRACE) satellites. Comparison with GOCE data shows that the TIMEGCM reproduced the cross‐track winds over the polar region very well. The model‐data comparison also revealed some differences, specifically, the simulations underestimated neutral mass density in the upper thermosphere above 300 km and overestimated the storm recovery tome by 6 h. These discrepancies indicate that some heating or circulation dynamics and potentially cooling processes are not fully represented in the simulations, and also that updates to some parameterization schemes in the TIMEGCM are warranted. Key Points: Unusually large thermospheric effects for a modest geomagnetic storm TADs have a strong latitude, longitude, and altitude dependence Finding two important thermospheric storm characteristics